Systematic Literature Review: Pendidikan Multikultural dengan Pendekatan Filosofis, Ideologis, dan Agama - Suksesiawati, Sisi (Journal of Innovation in Teaching and Instructional Media, 2025)
Multicultural education has become an important approach in promoting social inclusion, tolerance, and respect for diverse cultures, religions, and values. Data were collected from various reputable academic databases, such as Scopus, Web of Science, and Google Scholar, with inclusion criteria covering publications in highly reputable journals from 2020 to 2024. The results show that the philosophical approach is able to build a strong theoretical basis in understanding the meaning of diversity, the ideological approach plays a role in shaping inclusive education policies, while the religious approach shows effectiveness in promoting the values of tolerance and spirituality in learning. However, some key challenges were found, including potential cultural bias, lack of teacher training and resistance to faith-based approaches in secular areas. The study also identified research gaps in integrating the three approaches holistically, particularly in the context of education in developing countries and conflict areas. The findings offer recommendations for future research, such as further exploration of the intersections of culture, gender and religion in the context of multicultural education. As such, this SLR provides a solid foundation for the development of innovative and global values-based multicultural education practices.